Exploration of physico-chemical parameters and ionic constituents from groundwater used in irrigation of Tangail district, Bangladesh - Aziz, Elina; Mia, Md Younus; Meghla, Nowara Tamanna (Research in Agriculture Livestock and Fisheries, 2016)
The study was conducted for exploration of physico-chemical parameters and ionic constituents of groundwater used in irrigation of four upazilas namely Tangail Sadar, Kalihati, Delduar and Nagarpur upazila of Tangail district during the months of March, April and May of 2015. The physico-chemical parameters (pH, EC and TDS), ionic constituents (Ca2+, Mg2+, Na+, K+, Cl-, CO32-, HCO3-, PO43- and SO42-) and trace metal (Fe and Mn) were analyzed to assess the quality of irrigation in relation to soil properties and crop growth. The pH of groundwater indicates slightly alkaline in nature. As regards to EC the groundwater was in good class and medium salinity hazards in quality for irrigation and the concentration of TDS indicates water as fresh water. The concentration of Ca2+, Mg2+, Na+, K+, Cl-, CO32-, HCO3-, PO43- and SO42- of groundwater were recorded within the permissible limit for irrigation and these ions might not create hazardous impact on soil ecosystem for growing crops. The trace amount of Fe and Mn was detected in irrigation water. In the study area, the groundwater was within the recommended limit and would not create problem for irrigation and that have not long term effects on irrigating agricultural crops which could be safely used for irrigation purposes. Res. Agric., Livest. Fish.3(1): 115-119, April 2016